IMPROVEMENT OF ENERGY EFFICIENCY OF LOW-RISE RESIDENTIAL BUILDINGS AND FEATURES OF TECHNOLOGICAL SOLUTIONS (Conferencea, 2022)
Currently, existing buildings have a very low energy efficiency class. Many foreign countries are already actively using energy-saving technologies. The best indicators are observed in Germany. Germany is a recognized world leader in energy and resource saving, even though the share of alternative energy sources is about 16%, while in Austria this figure reaches 70% [1].